Macerated fetus in goat - MEHTA, VISHAL; VERMA, MANOJ KUMAR; BHATT, LENIN; PANDEY, VIJAY; BHARTI, MANOJ (The Indian Journal of Animal Reproduction, 2005)
A rare case of macerated fetus in a goat is reported. The macerated fetus was placed in the distal end of vagina, which wu removed, with help of sterilized swab holder through vaginal speculum. Prostaglandin and antimicrobial treatment was followed which resulted in removal of few left out bone pieces.